Advanced 3D “Modeling” and “Printing” for the Surgical Planning of a Successful Case of Thoraco-Omphalopagus Conjoined Twins Separation - Inserra, Alessandro; Borro, Luca; Spada, Marco; Frediani, Simone; Secinaro, Aurelio (Frontiers in Physiology, 2020)
The surgical separation of two Conjoined Twins is a particularly complex operation. The surgery times are particularly long and post-operative complications are very frequent in this type of operation. We report a clinical case of surgical separation of two thoraco-omphalopagus conjoined twins in which, thanks to the use of 3D technology, we were able to significantly reduce the operative time and favor the clinical outcomes of patients. We performed a 3D reconstruction of the anatomical parts involved in congenital fusion from co-registred CT and MRI images. We obtained the virtual anatomical models of the patients thanks to which we were able to estimate the exact position of virtual resection plans for both the general separation and for the hepatic splitting procedure. Subsequently we printed in 3D the anatomical models of the thoracic cage and the sternum, of the liver with the plane of hepatic resection and finally we printed the entire anatomical model of the two patients with multicolors and multimaterials organs represented. The use of 3D printing has allowed a reduction of 30% of the surgert time with a favorable outcome for the patients. Two years after the operation, the patients do not present any type of deficit and have a normal life without any significant complication.